Racial and Ethnic Disparities in Genetic Testing at a Hereditary Breast and Ovarian Cancer Center - Chapman-Davis, Eloise (J Gen Intern Med, 2020)
BACKGROUND: Prior studies suggest that referral to genetic counseling and completion of genetic testing vary by race/ethnicity; however, the data are limited. OBJECTIVE: We sought to evaluate patterns of genetic testing and clinical outcomes across race/ethnicity at a hereditary breast and ovarian cancer center. DESIGN: The medical records for all patients undergoing genetic assessment at a hereditary breast and ovarian cancer center were reviewed and stratified by self-reported race/ethnicity (non-Hispanic White, Hispanic, non-Hispanic Black, and Asian). PARTICIPANTS: A total of 1666 patients met inclusion criteria (non-Hispanic Whites, 1367; Hispanics, 85, non-Hispanic Blacks, 101; Asians, 113). MAIN MEASURES: Demographics, patient characteristics, and referral patterns for patients who underwent genetic testing were analyzed using Kruskal-Wallis tests, chi-square test, or Fisher’s exact tests, stratifying by self-reported race/ethnicity. Pathogenic mutations and variants of unknown significance (VUS) were reviewed. Outcomes of patients with genetic mutations and personal history of breast and/or gynecologic malignancies were compared. KEY RESULTS: Non-Hispanic Whites were more likely to be referred due to family cancer history compared to all other ethnicities while Non-Hispanic Blacks, Hispanics, and Asians were more likely to be referred due to personal history of cancer (p < 0.001). Non-Hispanic Blacks and Hispanics were more likely to have advanced-stage cancer at the time of genetic testing (p < 0.02). Rates of mutations did not differ by race/ethnicity when Ashkenazi Jewish patients were excluded (p = 0.08). Among patients found to have a BRCA1/2 mutation, Non-Hispanic Whites were more likely to undergo cancer screening and risk-reducing surgery compared with all other ethnicities (p = 0.04). CONCLUSIONS: Minority patients were more likely to utilize genetic services following a cancer diagnosis and less likely due to family cancer history, suggesting a missed opportunity for mutation detection and cancer prevention in this population. Efforts to eradicate racial/ethnic disparities in early access to genetic testing and guided cancer prevention strategies are essential. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-020-06064-x) contains supplementary material, which is available to authorized users.